Yolanda Arroyo Pizarro: epistemologias negras caribenhas. - Cristian Souza Sales (Nepan editor, 2021)
This text invests in the discussion about the epistemic production established by contemporary black Caribbean intellectuals. For this study, select an essay from the collection Tongas, palenques y quilombos: ensaios y columnas de afroresistencia by Yolanda Arroyo Pizarro (2013). It is a work consisting of essays, confe-rences and interviews in which the Puerto Rican author revisits the colonial past in the Hispanic Caribbean and, in addition, reveals stories of women’s insurgencies desde las ancestras. Based on these considerations, it demonstrates how other narratives come into dispute with the official historiography. That said, the article argues that Arroyo Pizarro proposes new political-epistemic articulations and constructions in opposition to hegemonic epistemologies. Therefore, in order to seek theoretical references relevant to the understanding of the text within the possibility of thinking about the proposition of black Caribbean epistemologies; political--epistemic insurgency; black epistemic insurgencies; dialogues with thinkers Catherine Walsh (2008, 2009) and Grada Kilomba (2019).